Application of quasiconformal mapping methods to the investigation of the explosive processes impact on the environment - Malash, Kateryna Mykolaiivna; Bomba, Andrii Yaroslavovych (Моделювання, керування та інформаційні технології, 2019)
The mathematical models used to study explosive processes are given. A class of problems investigating the influence of explosive processes on the environment by the quasiconformal mappings numerical methods are outlined and their practical application are described